2012
DOI: 10.1002/jssc.201101031
|View full text |Cite
|
Sign up to set email alerts
|

Tracking antiangiogenic components fromGlycyrrhiza uralensisFisch. based on zebrafish assays using high‐speed countercurrent chromatography

Abstract: Tracking antiangiogenic components fromGlycyrrhiza uralensis Fisch. based on zebrafish assays using high-speed countercurrent chromatography Natural products are some of the most important sources of lead compounds for drug discovery. The advanced isolation technique of lead compounds of natural origin using therapeutically relevant bioassays is capable of enhancing work efficiency from complex multiconstituent extracts. In the present study, a bioassay-guided isolation strategy combined with bioactivity scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…Glycyrrhetinic acid (50 and 100 μM/L) has been shown to inhibit expression of intercellular adhesion molecule 1 in TNF-α-activated endothelial cells by interrupting the c-Jun N-terminal kinase/c-Jun and IκB/NF-κB signaling pathways; thus, this compound may be useful for the treatment of inflammatory vascular diseases (Chang et al, 2010). Several studies have reported that licochalcone A , isolicoflavonol (Han et al, 2012), and isoliquiritigenin (Cao et al, 2010;Han et al, 2012;Jhanji et al, 2011) have antiangiogenic activity in different models of angiogenesis. Additionally, DGC has been shown to have significant cardiovascular protection effects in experimental models; for example, it suppressed cell migration and the dissociation of actin filaments by plateletderived growth factor in human aortic smooth muscle cells and in a rat vascular balloon injury model, and it inhibited excessive reduction of luminal diameters and neointimal formation (Kim et al, 2013a).…”
Section: Cardiovascular Studiesmentioning
confidence: 99%
“…Glycyrrhetinic acid (50 and 100 μM/L) has been shown to inhibit expression of intercellular adhesion molecule 1 in TNF-α-activated endothelial cells by interrupting the c-Jun N-terminal kinase/c-Jun and IκB/NF-κB signaling pathways; thus, this compound may be useful for the treatment of inflammatory vascular diseases (Chang et al, 2010). Several studies have reported that licochalcone A , isolicoflavonol (Han et al, 2012), and isoliquiritigenin (Cao et al, 2010;Han et al, 2012;Jhanji et al, 2011) have antiangiogenic activity in different models of angiogenesis. Additionally, DGC has been shown to have significant cardiovascular protection effects in experimental models; for example, it suppressed cell migration and the dissociation of actin filaments by plateletderived growth factor in human aortic smooth muscle cells and in a rat vascular balloon injury model, and it inhibited excessive reduction of luminal diameters and neointimal formation (Kim et al, 2013a).…”
Section: Cardiovascular Studiesmentioning
confidence: 99%
“…For that, there was exposure of the zebrafish to compounds known to cause specific effects such as anti-convulsant activity [39], glucose uptake [45], pro-angiogenesis [36,37], antiangiogenesis [19,44], or estrogenic effects [52,56]. Regarding negative control conditions, most of the studies reported the testing of solvent controls in the same concentration as for the respective sample testing [19,32,34,35,[38][39][40]43,44,47,[49][50][51]53,55]. Some studies have additionally evaluated a medium only condition in addition to the solvent control [36,37,42,54,56,57].…”
Section: Positive/negative Controls and Biotesting Of Blanksmentioning
confidence: 99%
“…For Environmental toxicology Sediment extracts [50], industrial effluents [33], rubber tyre leachates [32], oil sand process waters [57] Natural products Cyanobacteria and algae extracts [47], seaweed hydrolysates [48] Acute and developmental toxicity Lethal and morphological endpoints Environmental toxicology Sediment extracts [51], soil extracts [53], microalgae extracts [54], cyanobacteria extracts [55], river pore water extract [58] Natural products Bacteria extracts [46] Developmental toxicity Phenotypic endpoints Natural products Plant extracts [41] Anti-or pro-angiogenesis ISV formation and/or function in wild-type or fli1:EGFP zebrafish Natural products Plant extracts [19,[36][37][38][42][43][44] Anti-angiogenesis and anti-inflammatory ISV outgrowth in fli1:EGFP, leukocyte migration after tail transection Natural products Plant extracts [40] Glucose uptake Uptake of fluorescein-tagged glucose bioprobe…”
Section: Teratogenesis and Developmental Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Angiogenic/anti-angiogenic Lam et al, 2008;He et al, 2009a;He et al, 2009b;Hong et al, 2009;He et al, 2010;Alex et al, 2010;KRILL et al, 2010;Zhu et al, 2011;Liu et al, 2011;Crawford et al, 2011;Tse et al, 2012;Zhong et al, 2012;He et al, 2012;Zhang et al, 2012;Han et al, 2012;Yu et al, 2013;Ba et al, 2013;Lee et al, 2013;Yahg et al, 2013;Fan et al, 2013;Yue et al, 2013, Da-Song et al, 2014Zhou et al, 2014;Germano et al, 2014Lai et al, 2015Antithrombotic activity Song et al, 2012Shi et al, 2015anticonvulsant Orellana-Paucar et al, 2012Buenafe et al, 2013;Challal et al, 2014Anti-inflammatory Kao et al, 2010Bohni et al, 2013;Wang et al, 2013Antilipemic Jin et al, 2011Kim et al, 2012;Pardal et al, 2014;Littleton et al, 2014Melanogenic Kim et al, 2008Ding et al, 2011;Park et al, 2013;Kim et al, 2014;Wang et al, 2014Neurodegenerative diseases Zhang 2012Chong et al, 2013;…”
Section: Activity Assayed In Zebrafish Model Referencesmentioning
confidence: 99%